2011
DOI: 10.2478/s13386-011-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in SAR palaeodoses due to spatial heterogeniety of natural beta dose

Abstract: Abstract:In luminescence dating of sediments, Mayya et al. (2006) pointed out that at single grain level, the beta dose for quartz grains is heterogeneous. This heterogeneity arises due the fact that the total potassium in sediment is contributed by few feldspar grains with up to 11-14% stoichiometric potassium (Huntley and Baril, 1997). Beta particles have a range of ~2 mm, which is comparable to grain sizes and inter-grain distances. This fact implies that the spatial fluctuation of beta emitters (Kfeldspars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Ages were computed using the mean values and also the leading edge method (Lepper and Mckeever, 2002) (Table 1). The computation of final ages was in accordance with the work of Chauhan and Singhvi (2011), which indicated that most dispersion in these samples was attributable to heterogeneity of the beta dose. In the present case where the K concentration ranges from 0.7% to 1.6%, the anticipated dispersion because of heterogeneity of the beta dose distribution is given by the minimum to maximum paleodose ratio of <10, and hence, we used the mean dose for the computation of ages.…”
Section: Methodssupporting
confidence: 85%
“…Ages were computed using the mean values and also the leading edge method (Lepper and Mckeever, 2002) (Table 1). The computation of final ages was in accordance with the work of Chauhan and Singhvi (2011), which indicated that most dispersion in these samples was attributable to heterogeneity of the beta dose. In the present case where the K concentration ranges from 0.7% to 1.6%, the anticipated dispersion because of heterogeneity of the beta dose distribution is given by the minimum to maximum paleodose ratio of <10, and hence, we used the mean dose for the computation of ages.…”
Section: Methodssupporting
confidence: 85%
“…A reduction in average dose rate and increased dispersion (Fig. 12) with a higher degree of heterogeneity is consistent with modelling simulations and calculations by Nathan et al (2003) and Chauhan and Singhvi (2011). In both sets of results for 316-2 there is one outlying (higher) dose rate measurement that may be associated with a grain source and, if so, its presence in the powdered sample is surprising but may be the result of ball-milling that was insufficient to disperse smaller grains such as zircons of the size observed in the SEM examination.…”
Section: Spatial Variation Of Beta Dose Ratesupporting
confidence: 74%
“…As the samples were from well-bedded sediments it is unlikely that this is due to post-depositional disturbance (Bateman et al, 2007). It could instead be caused by (i) microdosimetry heterogeneity within the dose rate (Chauhan and Singhvi, 2011), which is relatively low at these sites, (ii) the poor luminescence characteristics of the quartz in these samples, or (iii) poor bleaching. Given all samples are thought to have come from the same source and had the same potential mixing of sediments prior to deposition, it is unclear why only some samples would appear multimodal/skewed if the poor luminescence characteristics were the dominant cause of this.…”
Section: Osl Datingmentioning
confidence: 99%